Analisis Dan Perancangan Sistem Absensi Berbasis RFID Pada Majelis Tafsir Al-Qur’an (MTA) Perwakilan Kota Jambi - Sambodo, Prakoso Setyo; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2020)
The Majlis Tafsir Al-Qur'an Foundation (MTA) has several activities such as social service, blooddonation, health education and routine recitation which are held in all branches and representatives. Withthe large number of inmates and general people participating in the recitation activities, participants andthose not present at the recitation activities should be recorded and recapitulated in order to find out thenumber and activeness of the residents who come to the study. The data collection process will take along time because they have to be called one by one and ask the reason for the absence of residents. Toovercome this time-consuming problem, the researcher conducted a system analysis that was carried outwith the aim of designing a system of attendance prototype systems based on Radio FrequencyIdentification (RFID) to facilitate the data collection process and attendance reporting. In building thisattendance system using website-based programming using the PHP programming language and MySQLdatabase processing, but this research is only limited to the analysis and role of the system usingprototype modeling. This study produced a solution to the problem, namely the design of RFID-basedattendance systems, where all attendance and recap attendance processes are carried out in RFID-basedattendance systems so that the output is automatically present attendance report after the assisted residentsfinish attaching RFID tags. constraints on the attendance process for a long time.